Higa-onon Phrase Structure - Quidlat, Purita B. (The Archive, 2025)
Higa-onon or Iga-onon refers to the language spoken by some 3,000 Higa-onons living in Sitio Kalamalamahan, Barangay Rogongon, Iligan City. Rogongon which is about 35 kms. Away from the poblacion and accessible by logging trucks, is located close to the boundaries of Lanao del Norte and Bukidnon. The origin of the Higa-onon has yet to be ascertained. Based on an interview with the informants, the term Higa-onon comes from the word GAUN which means to rise. They claimed to have lived originally along the coastline of Lanao del Norte and Misamis Oriental but they moved ‘gaun’ to the upland following the route of the river banks to avoid conversion to Islam. The Higa-onons claimed that the Maranaos are the Islamized Higa-onons. Fieldwork on Higa-onon was conducted in Kalamalamahan, Rogongon, a community of about 3,000 Higa-onons. Information was obtained from Higa-onon informants who are conversant in Hiaga-onon and in Cebuano (the medium of communication between informants and the investigator).